Odpowiedzi

2009-12-08T16:02:00+01:00
Najlepsza Odpowiedź!
2009-12-08T16:26:01+01:00
6-(5-x)-4x dla x= (-2)
6-(5-x)-4x =6-5+x-4x=1-3x
1-3×(-2)=1+6=7

8z-2(5z+6)+7z-4 dla z= ¾
8z-2(5z+6)+7z-4 =8z-10z-12+7z-4=5z-16
5×¾-16=⁵/₄-¹⁶/₁=¹⁵/₄-⁶⁴/₄=-⁴⁹/₄=-12¼

4p-2(8-p²)+5p²-p dla p= ½
4p-2(8-p²)+5p²-p= 4p-16+2p²+5p²-p=7p²+3p-16
7×(½)²+3×½-16=7×¼+³/₂-¹⁶/₁=⁷/₄+⁶/₄-⁶⁴/₄=¹³/₄-⁶⁴/₄=⁵¹/₄=12¾

(x+y)-(x-y) dla x= 0,75, y=(-0,5)
(x+y)-(x-y)=x+y-x+y=2y x się zredukował
2×(-0,5)=-1

0,7a²-1,2b²-9,9c⁴ dla a= (-1), b= 7, c= 0
0,7a²-1,2b²-9,9c⁴=0,7×(-1)²-1,2×7²-9,9×0=0,7×1-1,2×49=0,7-58,8=-58,1